Cytotoxic triterpene from Barringtonia asiatica - Ragasa, Consolacion Y. (Animo Repository, 2014)
Triterpenes isolated from the dichloromethane extract of Barringtonia asiatica, namely, a mixture of betulinic acid (1) and 22-O-tigloylcamelliagenin A (2) in a 1 : 2 ratio and a mixture of 3β-olean-18-en-3-yl palmitate (7), 3β-urs-12-en-3-yl palmitate (8) and 3β-olean-12-en-3-yl palmitate (9) in a 4 : 1 : 2 ratio (isolated from the bark), as well as germanicol caffeoyl ester (3), germanicol trans-coumaroyl ester (4), germanicol cis-coumaroyl ester (5) and germanicol (6) (from the leaves), and a phenolic compound, verimol K (10) from the flowers, were assessed for cytotoxicity against a human cancer cell line, colon carcinoma (HCT 116), using the MTT assay. The mixture of 1 and 2 exhibited IC50 =8.0 μg · mL–1 against this cell line, while 6 exhibited an IC50 value of 29.6 μg · mL–1. The other compounds tested (3 – 5, 7 – 10) were inactive against the HCT 116 cell line. The mixture of 1 and 2 and compound 6 were further tested for cytotoxicity against the non-small cell lung adenocarcinoma (A549) cell line. The mixture of 1 and 2 and compound 6 exhibited IC50 values of 6.0 and 35.6 μg · mL–1, respectively. The cytotoxicity for the mixture of 1 and 2 may be attributed to betulinic acid (1), a known cytotoxic compound. © 2014, Springer Science+Business Media New York.